Measurements of Radon Concentrations Indwelling of Shrqat in Salah Dien, Iraq - Shaker M. Marbut; Yasir K. Mohammad; Rajaa S. Najim (Journal of Madenat Alelem University College, 2012)
High radon levels are present in granite and grandiosity rocks that spread in Makhol Mountains. Such materials are rich in uranium and widely used in the construction of dwelling in the Shrqat. In the present work, the concentration of radon was measured, by using CR-39 dosimeter. Results suggest that radon concentration range from 66.32 to 45.63 Bq/m3. The maximum value 80.32Bq/m3 and minimum value 24.2 Bq/m3, with standard deviation 12.67Bq/m3. The result provides a framework for future studies that include a large, broader survey of radon concentration in Salah Dein.